Japan real estate investment - Hines, Mary Alice (Quorum Books, 2001)
Annotation "Based upon extensive research and experience, as well as expert input from international real estate professionals, Hines identifies the crucial characteristics, risks, and hazards of investment in Japanese real estate and investment elsewhere - subtleties that outside investors must grasp for success in Japanese markets. Hines shows how the Japanese economic climate is affecting the real estate market, how foreign investors are influencing Japanese property valuation and valuation systems, and why the financing of real estate in Japan through loan and equity securitization is on the rise. Real estate professionals with be particularly interested in Hines' coverage of commercial and residential property, while specialists with other interests will also get an unusual view of Japanese urban planning, land development, and tenure changes over time. Her book, the only up-do-date analysis in English of the subtleties of the real estate enterprise in Japan, is an essential resource for international real estate professionals, and a valuable guide for corporate international finance, investment and banking executives with interests in Japan."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Keywords: Real estate investment -- Japan.; Immeubles -- Investissements -- Japon.; BUSINESS & ECONOMICS -- Investments & Securities -- Real Estate.; Real estate investment; Japan; Investeringen.; Onroerend goed.